PHYTOCHEMICAL SCREENING AND ANTIMICROBIAL EXTRACTS ACTIVITY OF CALADIUM BICOLOR (Quantum Journal of Engineering, Science and Technology, 2021)
This study investigated the phytochemical composition and antimicrobial activities of ethanol and methanol leaf, stem and root extracts of Caladium bicolor (Aiton) Vent against some clinical pathogens. The ethanol and methanol extracts of the plant parts were prepared by adding separately 10g, 20g, 30g and 40g of the leaf, stem and root powder of C. bicolor into 100ml if ethanol and methanol respectively. All extracts of the plant parts at varying concentrations showed antifungal activity against the test fungi. Ethanol leaf extract showed between slightly (4.23+0.05–19.30+0.65) and moderately effective (25.08+0.06–31.44+0.10) inhibition on the mycelial growth of all the test fungi. Ethanol stem extract had slightly effective (2.07+0.01–16.00+0.08) inhibition on the test fungi. Ethanol root extract had slightly effective (2.05+0.06–12.60+0.15) inhibition on the test fungi. Also, methanol leaf extract showed between slightly (2.30+0.06–18.10+0.11) and moderately effective (20.28+0.01–21.02+0.04) inhibition respectively. Methanol stem extract had slightly effective (4.03+0.08–14.03+0.77) inhibition on the test fungi. Methanol root extract had slightly effective (1.00+0.06–11.40+0.09) inhibition on all the test fungi. The phytochemical analysis was done using standard techniques. Data were analysed using Analysis of Variance (ANOVA) to test for significance. Means were separated using Duncan’s Multiple Range Test (DMRT) at 5% level of probability using Statistical Analysis Software (SAS) package. This study showed that ethanol and methanol extracts of leaf, stem and root of C. bicolor were able to inhibit the pathogenic fungi hence the fungitoxic potentials of these extracts can provide an alternative to synthetic fungicides since it is less expensive, environmental friendly and easy to prepare.
Keywords: phytochemical; antimicrobial; extracts; caladium bicolor